A note on the location of poles of meromorphic functions - Sanjib Kumar Datta; Tanchar Molla (Journal of Hyperstructures)
A meromorphic function on an open set D contained in the finite complex plane C is of the form of the ratio betweentwo analytic functions defined on D with denominator not identically zero. Poles of meromorphic functions are those zeros of the denominator where numerator does not vanish. Finding all poles of a meromorphic function is too much difficult. So, it is desirable to know a region where these poles lie. In the paper we derive a region containing all the poles of some meromorphic functions. A few examples with related figures are given here to validate the results obtained.